2023
DOI: 10.1007/s43621-023-00122-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing access to basic water, sanitation, and hygiene (WASH) services in schools of Bishoftu Town, Ethiopia: a cross-sectional study

Abstract: Access to basic water, sanitation and hygiene services is the most effective mechanism to reduce many infectious diseases. WASH in schools related to better educational outcomes although adequate water, sanitation, and hygiene services were unavailable to millions of school-age children in Ethiopia. Therefore, it is crucial to assess the level of WASH coverage and identify factors affecting access to basic water, sanitation, and hygiene services. A cross-sectional study was carried out among 82 school faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The school basic hygiene service was a statistically significant association with teaching programs and training availability in Addis Ababa schools. This finding was supported by a study done in Bishoftu schools 20 and studies done in Indonesia by Karon. 23…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The school basic hygiene service was a statistically significant association with teaching programs and training availability in Addis Ababa schools. This finding was supported by a study done in Bishoftu schools 20 and studies done in Indonesia by Karon. 23…”
Section: Discussionsupporting
confidence: 66%
“…A study done in Bishoftu town schools' found that about 74.7% had access to basic drinking water, 61.3% had access to sanitation facilities, and 37.3% had access to hygiene services. 20 Another study in Kimbibit Woreda revealed that many schools had poor WASH facilities, with a latrine seat ratio of 60:1, simple pit latrines in 70.8% of schools, only 33.3% schools had sex separated latrines, and only 6.3% had handwashing facilities near the latrine, with none of these facilities had a water supply and soap for handwashing. 21 The progress of WASH services in public primary schools in the South Gondar zone of Northern Ethiopia has also been limited, with only 68.8% of urban students having access to basic drinking water, 66.7% had access to sanitation services, and 35.4% had access to handwashing facilities.…”
Section: Environmental Health Insightsmentioning
confidence: 99%
“…The investigation was conducted in Bishoftu town. Bishoftu is 44 km from the capital city of Addis Ababa 23,24 . The crater lakes and large swamp areas are part of Bishoftu town's dominant features and play an important role in the area's rapid economic and socioeconomic development.…”
Section: Methodsmentioning
confidence: 99%
“…This investigation was performed in Bishoftu town, Oromia National Regional State, Ethiopia. It is located at a distance of 44 km from the capital Addis Ababa 29. The town is clustered into nine urban kebeles (administrative units) and five rural kebeles with a total population of 171 227 30.…”
Section: Methodsmentioning
confidence: 99%
“…The town is clustered into nine urban kebeles (administrative units) and five rural kebeles with a total population of 171 227 30. The latitude and longitude of Bishoftu town are 8.734650 and 39.008533, respectively 31. The elevation of the city is 1920 m above sea level 32.…”
Section: Methodsmentioning
confidence: 99%